2021
DOI: 10.1002/mus.27250
|View full text |Cite
|
Sign up to set email alerts
|

Minimal important differences and self‐identifying treatment response in chronic inflammatory demyelinating polyneuropathy

Abstract: Introduction/Aim: The use of outcome measures is recommended for chronic inflammatory demyelinating polyneuropathy (CIDP). Implications of minimal important differences (MID) to ascertain responder status are unknown. The reliability of patient-reported treatment-response in relation to clinically relevant change is also unknown.Methods: We retrospectively studied 72 subjects with "definite" or "probable" CIDP evaluated at pre-specified time-intervals pre-and post-treatment. We derived MID and the minimum dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 31 publications
1
9
1
Order By: Relevance
“…The former approach is commonly applied in clinical practice and has been used in comparable cohort studies 10,16 . Frequent deviations in the i‐RODS above 4 logit points observed in our clinically stable cohort questions the reliability of this measurement in the individual, or suggests that the true MCID for the i‐RODS is higher than this value which is supported by recent patient‐reported treatment response analysis proposing MCID for the i‐RODS at 8 points 20 …”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The former approach is commonly applied in clinical practice and has been used in comparable cohort studies 10,16 . Frequent deviations in the i‐RODS above 4 logit points observed in our clinically stable cohort questions the reliability of this measurement in the individual, or suggests that the true MCID for the i‐RODS is higher than this value which is supported by recent patient‐reported treatment response analysis proposing MCID for the i‐RODS at 8 points 20 …”
Section: Discussionsupporting
confidence: 59%
“…10,16 Frequent deviations in the i-RODS above 4 logit points observed in our clinically stable cohort questions the reliability of this measurement in the individual, or suggests that the true MCID for the i-RODS is higher than this value which is supported by recent patient-reported treatment response analysis proposing MCID for the i-RODS at 8 points. 20 We found grip strength to fluctuate less than i-RODS and MRC-SS. However, studies of daily grip strength measurement have indicated that averaging consecutive readings over 3 days is required to smooth out random variation and reliably detect change.…”
Section: Discussionmentioning
confidence: 51%
“…This implies that variability exceeding MCIDs in stable patients is also common in clinical care. Another study of CIDP patients investigated the minimum detectable change (MDC), 27 which is conceptually similar to the limits of variability used in our study, as both reflect the threshold of changes beyond that what can be observed in stable patients. The MDC of I‐RODS was smaller than limits of variability in our data 27 .…”
Section: Discussionmentioning
confidence: 97%
“…Another study of CIDP patients investigated the minimum detectable change (MDC), 27 which is conceptually similar to the limits of variability used in our study, as both reflect the threshold of changes beyond that what can be observed in stable patients. The MDC of I‐RODS was smaller than limits of variability in our data 27 . Also, contrary to our results, the distribution‐based MCID value of grip strength and the I‐RODS exceeded the MDC, 27 indicating that clinically meaningful changes can be distinguished from random variability.…”
Section: Discussionmentioning
confidence: 97%
“…In this issue of Muscle and Nerve, Rajabally and colleagues report the results of a retrospective study that aims to better understand how response to CIDP treatment can be defined in clinical practice. 12 Outcomes that have been historically collected in clinical trials including strength impairment (Medical Research Council [MRC] sum score, grip strength using a handheld dynamometer) and disability (overall neuropathy limitations scale [ONLS] disability score, I-RODS disability score) were obtained pre-and post treatment. Additionally, after treatment all participants were asked a standard question to capture the patient perception of treatment response: "Do you feel you have been improved by the treatment for your CIDP?".…”
mentioning
confidence: 99%